2019
DOI: 10.1111/jocn.14793
|View full text |Cite
|
Sign up to set email alerts
|

Perceived HIV‐related physical fatigue, sociodemographic characteristics and physical activity: A cross‐sectional study

Abstract: Aims and objectivesTo get a deeper understanding of correlates of perceived HIV‐related fatigue by exploring its associations with sociodemographic characteristics and physical activity level of HIV‐infected people.BackgroundPrevious studies on HIV‐related fatigue have mainly focused on physiological and psychological characteristics, but few have considered its associations with sociodemographic variables. In addition, while physical activity has been found to reduce acute fatigue among HIV‐infected people, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 65 publications
5
11
0
Order By: Relevance
“…The present study also found that female patients were more likely to perceive fatigue than men. This finding is similar to the studies conducted in South Africa, 37 France, 51 and a systematic review. 13 The mean age of women in this was lower than men, the majority of those who were diagnosed with anaemia and weight loss were women.…”
Section: Discussionsupporting
confidence: 91%
“…The present study also found that female patients were more likely to perceive fatigue than men. This finding is similar to the studies conducted in South Africa, 37 France, 51 and a systematic review. 13 The mean age of women in this was lower than men, the majority of those who were diagnosed with anaemia and weight loss were women.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, severity of insomnia had been associated with greater fatigue, and depression may contribute to both insomnia and fatigue [31]. Being physically active has also been reported as a protective factor for having fatigue among HIVpositive patients [19,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, severity of insomnia had been associated with greater fatigue, and depression may contribute to both 4 insomnia and fatigue [31]. Being physically active has also been reported as a protective factor for having fatigue among HIV-positive patients [19,32,33].…”
Section: Introductionmentioning
confidence: 99%